2015
DOI: 10.1371/journal.pone.0133474
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation Reveals Altered Brain Perfusion Patterns in Somnambulism

Abstract: BackgroundDespite its high prevalence, relatively little is known about the pathophysiology of somnambulism. Increasing evidence indicates that somnambulism is associated with functional abnormalities during wakefulness and that sleep deprivation constitutes an important drive that facilitates sleepwalking in predisposed patients. Here, we studied the neural mechanisms associated with somnambulism using Single Photon Emission Computed Tomography (SPECT) with 99mTc-Ethylene Cysteinate Dimer (ECD), during wakefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…Interestingly, reduced brain perfusion in frontal and parietal regions persisted during resting-state wakefulness. These findings replicate the evidence from an earlier study [45], which hypothesised these areas to be responsible for the daytime impairment experienced in NREM parasomnia patients.…”
Section: Functional Imaging Studiessupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, reduced brain perfusion in frontal and parietal regions persisted during resting-state wakefulness. These findings replicate the evidence from an earlier study [45], which hypothesised these areas to be responsible for the daytime impairment experienced in NREM parasomnia patients.…”
Section: Functional Imaging Studiessupporting
confidence: 90%
“…An overall reduction in brain metabolism when compared to wakefulness is the most striking characteristic [44]. This reduction is most obvious in brain regions responsible for a range motor and cognitive functions: brainstem, thalamus, basal ganglia, basal forebrain, prefrontal cortex, anterior cingulate cortex and precuneus [44,45]. As functional imaging studies have shown, there are some crucial differences in the characteristics of SWS in healthy controls and NREM parasomnia patients.…”
Section: Functional Imaging Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in associative visual areas during wakefulness might also predispose sleepwalkers to experience visual percepts during sleep. 74 …”
Section: 71mentioning
confidence: 99%
“…Tc-ECD SPECT in order to investigate brain structures associated with somnambulism [29]. Ten sleepwalkers and 10 healthy controls were recruited and scanned after a night of sleep.…”
Section: Neuroimaging In Doamentioning
confidence: 99%